Long-Term Outcomes of Primary Intraocular Lens Implantation for Unilateral Congenital Cataract. (1st November 2016) - Magli, Adriano; Forte, Raimondo; Carelli, Roberta; Rombetto, Luca; Magli, Giulia
Abstract: Purpose : In congenital cataracts, the need for early intervention is well established to prevent visual deprivation and amblyopia. We evaluated patients with unilateral amblyogenic congenital who had undergone simultaneous cataract removal and intraocular lens implantation. Methods : We retrospectively reviewed all patients operated on between 1990 and 2010 at the Pediatric Eye Department of the University Federico II of Naples (Italy). Minimum follow-up for inclusion was 48 months. Results : 52 patients (28 females, 24 males, mean age at surgery 9.0 ± 4.5 months, range 2–21 months) were included in this retrospective review. Mean follow-up was 100.7 ± 57.0 months (range, 48–270 months). At last visit, mean BCVA in the operated eyes was 0.65 ± 0.4 (range, 0.04–1.3) LogMAR and 40 patients (76.9%) had strabismus. In patients undergoing surgery at an age >12 months, BCVA was significantly lower (0.92 ± 0.4 LogMAR versus 0.60 ± 0.4 LogMAR, p  = 0.01), although development of myopic shift was less frequent (61.5% versus 43.5%, p  = 0.03). BCVA at last visit was higher in patients with a first stable pseudophakic SE between +1D and +3D ( p  = 0.02). Conclusions : Worse final BCVA, despite less frequent development of myopic shift, was observed when surgery was performed after 12 months of age. A hyperopic correction in first stable pseudophakic SE seems advisable.